Headhunting Digital Talents and Clients in Marketing’s Perspective in Binar Academy - Della Suwarno Putri; Istyakara Muslichah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study examined headhunting digital talents and clients in marketing’s perspective in Binar Academy. Binar Academy is the pioneer of digital talent factory and one step solution for digital transformation and talent development in Indonesia. This study used a qualitative method by interviewing 5 employees in the Job Connect team. This study explained the challenges of inbound and outbound marketing strategies. This study also described the way of the Job Connect team in engaging customers. The results of this study showed that the challenges of inbound marketing are familiarity, the quality of content, and the target market. While the challenges of outbound marketing are brand awareness, the persuasiveness of mass messages, and communication skill. Last, the way to engage customers that used in Job Connect teams are keeping the client in loop, making engagement sessions, and making an attractive content & sharing insight.